2008
DOI: 10.1097/01.asw.0000323532.98003.26
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study Involving the Use of a Human Acellular Dermal Regenerative Tissue Matrix for the Treatment of Diabetic Lower Extremity Wounds

Abstract: This multicenter, retrospective study presents the use of a human acellular dermal regenerative tissue matrix as an alternative treatment for 100 chronic, full-thickness wounds of the lower extremity in 75 diabetic patients. Comorbidities included cardiac disease (86.0%), neuropathy (86.0%), peripheral vascular disease (82.0%), infection (54.0%), obesity (51.0%), and osteomyelitis (37.0%). Wound locations included the foot (86.0%), ankle (8.0%), and lower extremity (6.0%). Mean wound age was 20.4 weeks (1.3-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 8 publications
1
46
0
2
Order By: Relevance
“…The allografts are harvested from screened donors, and each is prepared with proprietary processes to decellularize and cryopreserve the dermis while maintaining the natural structure of the collagen and ECM. [240][241][242][243][244][245] As with the aforementioned ECM products, the dermal matrices serve as scaffolds for cellular repopulation and angiogenesis, with varying degrees of incorporation into the recipient wound bed. 246,247 One of these cryopreserved dermal allografts, referred to as a human skin allograft, claims that both the extracellular and cellular components are preserved during the minimal processing.…”
Section: Biological and Bioengineered Therapiesmentioning
confidence: 99%
“…The allografts are harvested from screened donors, and each is prepared with proprietary processes to decellularize and cryopreserve the dermis while maintaining the natural structure of the collagen and ECM. [240][241][242][243][244][245] As with the aforementioned ECM products, the dermal matrices serve as scaffolds for cellular repopulation and angiogenesis, with varying degrees of incorporation into the recipient wound bed. 246,247 One of these cryopreserved dermal allografts, referred to as a human skin allograft, claims that both the extracellular and cellular components are preserved during the minimal processing.…”
Section: Biological and Bioengineered Therapiesmentioning
confidence: 99%
“…TERM approach using acellular dermal graft has also been described [31]. This technique allies tissue-engineered matrices to the cells and GFs present in the human recipient following transplantation.…”
Section: Introduction: Fundamentals Of Tissue Engineering and Regenermentioning
confidence: 99%
“…No RCTs exist for any other indications aside from DFU. Studies have shown a statistically signifi cant higher percentage of overall wound healing with the use of Graftjacket ( Brigido, 2006 ;Brigido, Boc, & Lopez, 2004 ;Martin, Sangalang, Wu, & Armstrong, 2005 ;Reyzelman et al, 2009 ;Winters et al, 2008 ).…”
Section: Reconstruction Departmentmentioning
confidence: 97%